THE INFLUENCE OF THE GENDER PERSONALITY OF THE MANAGER ON INTERPERSONAL RELATIONS IN PERSONNEL MANAGEMENT - Dilorom Abdullaevna Salieva; Karas Orzhanovich Kaziev (Galaxy International Interdisciplinary Research Journal, 2022)
The article highlights the essence of the research work in order to bring to life the relationship with employees in the management process, as well as the organizational abilities of leaders, to identify individual psychological characteristics inherent in the gender in the leader’s activities.